Crecimiento de dos especies forestales en el Varillal (km 14.5) de la carretera Iquitos Nauta, Loreto-Perú, 2022 - Padilla Yumbato, Jairo Efraín (2023)
The present study was carried out in a Varillal forest plantation, belonging to the Ministry of Agriculture, located at km 14.5 of the Iquitos highway, Nauta, understanding the District of San Juan Bautista, Province of Maynas, Department of Loreto. The objective was to evaluate the growth and increase of two forest species in the mentioned area. La evaluación del crecimiento e incremento de los parámetros observados se hizo en base al diseño simple al azar, con las especies como tratamientos y cinco repeticiones por tratamiento, aplicando posteriormente la prueba de Duncan al nivel de significación de 0.05. Twenty-five years after the forest plantation was established, the tornillo (Cedrelinga cateniformis) is higher in growth and average annual increase in height than the andiroba species (Carapa guianensis). Twenty-five years after the forest plantation was established, the Andiroba (Carapa guianensis) is higher in growth and mean annual increase in diameter than the tornillo species (Cedrelinga cateniformis). The growth and average increases in height and diameter of forest species are considered low, mainly due to the lack of maintenance of the plantation and related factors. The tornillo (cedrelinga cateniformis) has shown favorable growth in forest plantations and due to its high commercial value, it is the species that should be prioritized in reforestation programs.